CHARACTERISTICS OF ORIENTALISM STUDIES AND IMPLICATIONS FOR THE ISLAMIC WORLD - Sapariah, Jamiatun; Rezky, Laily; Ajmi, Syauhan; Abdul Aziz, Abdul Rashid (Yayasan Maslahatul Ummah Ilal Jannah, 2023)
This study aims to analyze the study of orientalism through a qualitative approach to literature study, which will be observed based on several indicators, namely in terms of understanding, characteristics, and implications for the Islamic world. Initially, Orientalism was understood as an understanding carried out by Westerners to explore the East, both in terms of religion and civilization. The study of Orientalism has a strong relationship with Western colonialism in the Eastern world, colonialism, imperialism, missionarism and Christianization movements. In its development, orientalism gave another color through the emergence of controversial things circulating about Islam such as damaging the real image of Islam, opportunities to enrich Islamic studies and introduce the original face of Islam rahmatan lilalamin, joy for the western world that began to recognize Islamic civilization, its contribution in the field of translation as well as Eastern scholarship, and encouragement in efforts to achieve peace. With this study we can also understand not always negative orientalists, but there are also those who purely as academics make themselves objective researchers. So that thefaith of Muslims in orientalism should not be shown through emotions, and diversity of judgments of Islam also exists. However, there is nothing wrong with staying vigilant and caring for aqidah by increasing faith in Allah SWT and making this motivation through the need for intention and deepening shahih knowledge, especially in the current era